Analysing some issues with SOX. (1st January 2013) - Sy, Aida
The Sarbanes-Oxley Act legislation (the SOX) was triggered by a series of market failures that were exemplified by the bankruptcy of Enron, whose accounting errors inflated earning by almost 600 million since 1994. With assets of 62 billion, Enron was the largest bankruptcy case in US history. The Enron collapse was dwarfed several months later by the massive fraud and bankruptcy filing of WorldCom in July 2002, with 100 billion in assets. The changes in internal control required by SOX's executive arm – the Public Company Accounting Oversight Board (PCAOB) – imposed costs, that have given rise to appeals to rollback or repeal the requirements (for small firms, overseas firms, etc). One emerging technology – analytic monitoring – offers a possible answer to this impasse. It tenders a family of solutions that are potentially cheaper and more effective than traditional systems of control.